189k views
2 votes
When f(x)=6x2−2x+2 , evaluate f(−1)
f(-1)=

1 Answer

4 votes

Answer:

f(-1) = 10

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Explanation:

Step 1: Define

f(x) = 6x² - 2x + 2

f(-1) is x = -1

Step 2: Evaluate

  1. Substitute in x: f(-1) = 6(-1)² - 2(-1) + 2
  2. Exponents: f(-1) = 6(1) - 2(-1) + 2
  3. Multiply: f(-1) = 6 + 2 + 2
  4. Add: f(-1) = 8 + 2
  5. Add: f(-1) = 10
User Deostroll
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.